2022
DOI: 10.1063/5.0087652
|View full text |Cite
|
Sign up to set email alerts
|

MoS2/SnO2 heterojunction-based self-powered photodetector

Abstract: A heterostructure of MoS2/SnO2 has been fabricated. A SnO2 film was deposited by Sn sputtering followed by oxidation of a Sn film in the ambient. Later, a MoS2 film was deposited on SnO2 by pulsed laser deposition. The built-in electric potential generated at the SnO2/MoS2 interface facilitates self-powered broadband photodetection ranging from the ultraviolet-visible to near-infrared (NIR) wavelength. Under NIR illumination, the device exhibits excellent photoresponse with a responsivity of 0.35 A W−1 and a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…S7, ESI†). 24,34 Consequently, due to the accumulation of electrons in the outer-surface MoS 2 nanosheets, more ionized oxygen can be attracted to be chemically adsorbed as O 2(ads) − on the surface of the MoS 2 /SnO 2 heterostructure, which leads to the enhanced gas sensing performance of the sensor. The sensing process can be described as follows:O 2 gas → O 2 ads O 2 ads + e − → O 2 ads − NO 2 gas + e ads − → NO 2 ads − NO 2 gas + O 2 ads − → NO 2 ads − + O 2 ads When the sensor is exposed to NO 2 gas, the NO 2 molecules adsorbed on the surface can capture free electrons to form NO 2 − ads .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S7, ESI†). 24,34 Consequently, due to the accumulation of electrons in the outer-surface MoS 2 nanosheets, more ionized oxygen can be attracted to be chemically adsorbed as O 2(ads) − on the surface of the MoS 2 /SnO 2 heterostructure, which leads to the enhanced gas sensing performance of the sensor. The sensing process can be described as follows:O 2 gas → O 2 ads O 2 ads + e − → O 2 ads − NO 2 gas + e ads − → NO 2 ads − NO 2 gas + O 2 ads − → NO 2 ads − + O 2 ads When the sensor is exposed to NO 2 gas, the NO 2 molecules adsorbed on the surface can capture free electrons to form NO 2 − ads .…”
mentioning
confidence: 99%
“…S7, ESI †). 24,34 Consequently, due to the accumulation of electrons in the outer-surface MoS 2 nanosheets, more ionized oxygen can be attracted to be chemically adsorbed as O 2(ads)…”
mentioning
confidence: 99%
“…Recently, our group has examined the photodetection behaviour of MoS 2 with ZnO 34 and SnO 2 . 31 Among these, the MoS 2 /ZnO photodetector did not exhibit self-powered photodetection due to the presence of a large barrier height at the heterointerface, which cannot be overcome by the built-in electric voltage. On the other hand, MoS 2 /SnO 2 exhibits self-powered photodetection due to the generated built-in voltage at the heterointerface, which is sufficiently high enough to facilitate the separation and transportation of charge carriers.…”
Section: Introductionmentioning
confidence: 98%
“…[24][25][26][27] Various research groups have integrated MoS 2 with semiconductor materials such as III-nitrides, other transition metal dichalcogenides, layered metal dichalcogenides, perovskites, and oxides ZnO, SnO 2 , SnO, and CuO. [28][29][30][31][32][33][34][35] Among these, the wide band gaps (3-4 eV), high chemical and thermal stability, low-cost synthesis, and environmentally compatible constituents make metal oxides better candidates to integrate with MoS 2 for photodetection applications with high figures of merit. Recently, our group has examined the photodetection behaviour of MoS 2 with ZnO 34 and SnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The response mechanism of the self-powered devices is analyzed based on the photovoltaic effect of the semiconductor heterostructures, where the built-in voltage generated at the junction/interface facilitates separation and driving of charge carriers (electrons and holes) when illuminated by photons of appropriate energy. 8,10,11 In this report, we present a novel self-powered photoresponse from a Ag-MoS 2 −Ag device with an MSM configuration, which displayed wide-band photodetection along with current polarity flipping at two different wavelengths of the incident light. An inquiry into the literature on photocurrent switching revealed that photothermoelectric effects, 4,12,13 light-intensity-induced photoswitching, 7 photochemical effects, etc.…”
Section: ■ Introductionmentioning
confidence: 99%